2002
DOI: 10.1161/hc0302.102572
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Preconditioning by Attenuated Activation of Myocardial ATP-Sensitive Potassium Channels in Elderly Patients Undergoing Coronary Angioplasty

Abstract: Background-The ischemic preconditioning response among elderly patients is known to be lower than in adult patients.Since mitochondrial ATP-sensitive potassium (K ATP ) channels exert preconditioning effects, we undertook this study to determine whether this attenuated activation of K ATP channels influences the reduced responsiveness of elderly patients to ischemic preconditioning. Methods and Results-Fifty-six patients undergoing angioplasty for a major epicardial coronary artery were randomly allocated to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
86
0
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(94 citation statements)
references
References 31 publications
3
86
0
5
Order By: Relevance
“…Cardiac function working heart with equal preload, afterload, and heart rate, the enhanced cardioprotection after exercise preconditioning was due to adaptations within the ventricle. Although several reports indicate that aging attenuates or abolishes the improved tolerance to I/R after ischemic preconditioning (1,2,12,20,24,29), those studies focused on the "early" stage of preconditioning, which does not require protein synthesis and lasts only 2-3 h after the preconditioning stimulus (5,19). In this regard, Abete et al (1) reported that a 6-wk swimming program restored the effectiveness of ischemic preconditioning in aged Wistar rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac function working heart with equal preload, afterload, and heart rate, the enhanced cardioprotection after exercise preconditioning was due to adaptations within the ventricle. Although several reports indicate that aging attenuates or abolishes the improved tolerance to I/R after ischemic preconditioning (1,2,12,20,24,29), those studies focused on the "early" stage of preconditioning, which does not require protein synthesis and lasts only 2-3 h after the preconditioning stimulus (5,19). In this regard, Abete et al (1) reported that a 6-wk swimming program restored the effectiveness of ischemic preconditioning in aged Wistar rats.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several studies conclude that HSP70 expression after heat stress is impaired in the heart of aged animals (for a review, see Ref. 30), and the cardioprotective benefits induced by ischemic preconditioning are attenuated or abolished with age (2,12,20,24,29). Thus the purpose of this study was to determine the effect of age on exercise-induced protection against I/R and on changes in cardioprotective proteins.…”
mentioning
confidence: 99%
“…In addition, several experimental and clinical investigations have addressed the issue of whether IPC occurs in aged hearts (1,2,28,40,46). The efficacy of IPC has been reported to be decreased or lost in senescent patients (2,28) and in aged animals (1,40).…”
Section: Effect Of Cr On Myocardial Ischemia-reperfusion Injury and Ipcmentioning
confidence: 99%
“…Hearts from senescent animals are more susceptible to ischemia than those from young animals (7,20,45). Recently, a number of investigators have demonstrated that the cardioprotective effect of ischemic preconditioning (IPC) is impaired in aged animals (1,2,28,40,46). Aging also loses the cardioprotection afforded by postconditioning (8).…”
mentioning
confidence: 99%
“…38 Mechanistic explanations for the loss of IPC efficacy with increasing age include decreased norepinephrine release in older hearts, 50 decreased connexin 43 and ability to generate adenosine triphosphate (ATP) in mitochondria, decreased gap junctions 51 and impaired activation of the ATP-sensitive potassium (K ATP ) channels. 52 Therefore, it is possible that the decreased efficacy of IPC of the liver in clinical trials could partly arise from enrollment of a significant proportion of elderly subjects/donors. For example, in our recent trial of IPC in DDLT, 46% of the donors were aged Ն50 years.…”
Section: Liver Transplantationmentioning
confidence: 99%